Shaping oral and intestinal microbiota and the immune system during the first 1,000 days of life - Zhu, Jie; He, Mingxin; Li, Simin; Lei, Yumeng; Xiang, Xiaochen; Guo, Zhi; Wang, Qiang (Frontiers in Pediatrics, 2025)
The first 1, 000 days of life, from the fetal stage of a woman's pregnancy to 2 years of age after the baby is born, is a critical period for microbial colonization of the body and development of the immune system. The immune system and microbiota exhibit great plasticity at this stage and play a crucial role in subsequent development and future health. Two-way communication and interaction between immune system and microbiota is helpful to maintain human microecological balance and immune homeostasis. Currently, there is a growing interest in the important role of the microbiota in the newborn, and it is believed that the absence or dysbiosis of human commensal microbiota early in life can have lasting health consequences. Thus, this paper summarizes research advances in the establishment of the oral and intestinal microbiome and immune system in early life, emphasizing the substantial impact of microbiota diversity in the prenatal and early postnatal periods, and summarizes that maternal microbes, mode of delivery, feeding practices, antibiotics, probiotics, and the environment shape the oral and intestinal microbiota of infants in the first 1, 000 days of life and their association with the immune system.